Content knowledge gathered by undergraduate students in Mathematics on Probability and Statistics based on data from Covid-19 (Revista BOEM, 2025)
In this article, we present the results of a study that aims to analyze the Content Knowledge mobilized by students on the topic of Probability and Statistics based on COVID-19 data. The study was developed with 16 students from a Mathematics undergraduate course at a federal educational institution in the state of Rio Grande do Sul, enrolled in the second semester of 2020 in a discipline that contemplates the discussion of different ways of organizing and presenting the Mathematics content in the final years of Elementary School. The data were collected through activities sent via Moodle and presentations in a virtual classroom, via Google Meet, containing three problems developed by the students on the Probability and Statistics content covered in Elementary School. Through a qualitative, interpretative analysis, we demonstrate how statistical thinking manifests itself in the face of the questions elaborated by the students. We also highlight the importance of using the question elaborating strategy, since this is one of the skills that Mathematics teachers must develop with their students throughout Elementary School and, therefore, we believe that activities that involve the discussion of themes and questions from the Mathematics curriculum and the practice of the future teacher are fundamental for the initial teacher education.
Keywords: content knowledge; statistical thinking; probability and statistics; elementary school